The Missing Link in Plant Histidine Biosynthesis: Arabidopsis myoinositol monophosphatase-like2 Encodes a Functional Histidinol-Phosphate Phosphatase(1)([W])([OA]) - Petersen, Lindsay N. (American Society of Plant Biologists, 2010)
Histidine (His) plays a critical role in plant growth and development, both as one of the standard amino acids in proteins, and as a metal-binding ligand. While genes encoding seven of the eight enzymes in the pathway of His biosynthesis have been characterized from a number of plant species, the identity of the enzyme catalyzing the dephosphorylation of histidinol-phosphate to histidinol has remained elusive. Recently, members of a novel family of histidinol-phosphate phosphatase proteins, displaying significant sequence similarity to known myoinositol monophosphatases (IMPs) have been identified from several Actinobacteria. Here we demonstrate that a member of the IMP family from Arabidopsis (Arabidopsis thaliana), myoinositol monophosphatase-like2 (IMPL2; encoded by At4g39120), has histidinol-phosphate phosphatase activity. Heterologous expression of IMPL2, but not the related IMPL1 protein, was sufficient to rescue the His auxotrophy of a Streptomyces coelicolor hisN mutant. Homozygous null impl2 Arabidopsis mutants displayed embryonic lethality, which could be rescued by supplying plants heterozygous for null impl2 alleles with His. In common with the previously characterized HISN genes from Arabidopsis, IMPL2 was expressed in all plant tissues and throughout development, and an IMPL2:green fluorescent protein fusion protein was targeted to the plastid, where His biosynthesis occurs in plants. Our data demonstrate that IMPL2 is the HISN7 gene product, and suggest a lack of genetic redundancy at this metabolic step in Arabidopsis, which is characteristic of the His biosynthetic pathway.